Influence of Type of Seedlings, Planting Methods and Nitrogen levels on Yield and Quality of Sugarcane Under Drip Fertigation - Gouri, V.; Devi, T. Chitkala; Bharathalakshmi, M. (International Journal of Bio-resource and Stress Management, 2019)
A field experiment was conducted for three consecutive years from 2013-14 to 2015-16 at Regional Agricultural Research Station, Anakapalle, Andhra Pradesh, India. The experiment was laid out in split plot design, planting methods as main plot treatments and levels of nitrogen as sub plot treatments under drip fertigation. The main plot treatments constitute paired row planting with single node seedlings, paired row planting with bud chip seedlings, dual row planting with single node seedlings, dual row planting with bud chip seedlings and normal planting with three budded setts. Sub plot treatments are 75% RDN, 100% RDN and 150% recommended dose of nitrogen supplied through drip. Pooled data analysis of three years indicated that planting of single node seed lings in dual rows of 150×45 cm2 (103.6 t ha-1) or paired rows of 60/120×60 cm (102.4 t ha-1) registered significantly higher cane yield as compared to the planting of bud chip seedlings in dual rows or paired rows and planting of three budded setts in furrows. Sugarcane cultivation with single node seedlings increased the cane yield to the tune of 5.0% compared to the normal planting under drip fertigation. However, bud chip seedlings also performed well in dual row planting. Application of nitrogen at 150% recommended dose through fertigation recorded significantly higher cane yield of 104.8 t ha-1 than 75% or 100% RDN.